Nano-composite Membranes and Zero Thermal Input Membrane Distillation for Seawater Desalination - Baghbanzadeh, Mohammadali (Université d'Ottawa / University of Ottawa, 2017)
In this PhD thesis, seawater desalination by Membrane Distillation (MD) has been explored from the perspective of process and membrane. Regarding the process, an innovative, energy efficient, and environmentally friendly Zero Thermal Input Membrane Distillation (ZTIMD) process was proposed. ZTIMD uses thermal energy stored in seawater, which makes the process sustainable by being independent of the external sources of thermal energy, which is one of the major contributors to the cost and energy consumption of conventional MD desalination processes. Economic feasibility study was carried out for the ZTIMD process, and it was demonstrated that drinking water could be produced with a cost of $0.28/m3, which is approximately half of the cost of conventional desalination processes. Regarding the membrane, novel MD membranes were developed through incorporation of nanomaterials in polyvinylidene fluoride (PVDF). Different nanomaterials including superhydrophobic SiO2, amine modified hydrophilic SiO2, CuO, and CaCO3 were used for this purpose. It was shown that membrane structure and consequently its performance could be affected by the nanoparticle properties, concentration, presence of backing material, PVDF blend ratio, and penetration time. In a best membrane developed in this work, almost 2500% increase was observed in the Vacuum Membrane Distillation (VMD) flux over that of the neat PVDF membrane at a feed temperature of 27.5 °C and vacuum pressure of 1.2 kPa, when 7.0 wt.% hydrophilic SiO2 nanoparticles were added into a PVDF membrane supported with Non-Woven Fabric (NWF) polyester. The membrane possessed near perfect selectivity.
Keywords: Desalination; Membrane distillation; Zero thermal input membrane distillation; Nanocomposite membrane